2020
DOI: 10.1534/g3.119.401035
|View full text |Cite
|
Sign up to set email alerts
|

Generating Stable Knockout Zebrafish Lines by Deleting Large Chromosomal Fragments Using Multiple gRNAs

Abstract: The CRISPR (clustered regularly interspaced short palindromic repeats) and Cas9 (CRISPR associated protein 9) system has been successfully adopted as a versatile genetic tool for functional manipulations, due to its convenience and effectiveness. Genetics lesions induced by single guide RNA (gRNA) are usually small indel (insertion-deletion) DNA mutations. The impact of this type of CRISPR-induced DNA mutation on the coded mRNA transcription processing and protein translation can be complex. Unexpected or unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Second, large indels may disrupt the sequencing PCR primers' binding sites, preventing amplification of such alleles. Third, the pooled RNPs may also lead to deletion of large sequences that span two loci being targeted ( Hoshijima et al, 2019 ; Kim and Zhang, 2020 ; Moreno-Mateos et al, 2015 ; Wu et al, 2018 ). To test the latter possibility, we Sanger sequenced amplicons from regions that span multiple targeted loci within slc24a5 .…”
Section: Resultsmentioning
confidence: 99%
“…Second, large indels may disrupt the sequencing PCR primers' binding sites, preventing amplification of such alleles. Third, the pooled RNPs may also lead to deletion of large sequences that span two loci being targeted ( Hoshijima et al, 2019 ; Kim and Zhang, 2020 ; Moreno-Mateos et al, 2015 ; Wu et al, 2018 ). To test the latter possibility, we Sanger sequenced amplicons from regions that span multiple targeted loci within slc24a5 .…”
Section: Resultsmentioning
confidence: 99%
“…Second, large indels may disrupt the sequencing PCR primers binding sites, preventing amplification of such alleles. Third, the pooled RNPs may also lead to deletion of large sequences that span two loci being targeted (Hoshijima et al, 2019;Kim and Zhang, 2020;Moreno-Mateos et al, 2015;Wu et al, 2018). To test the latter possibility, we Sanger sequenced amplicons from regions that span multiple targeted loci within slc24a5.…”
Section: Sequencing Of Targeted Loci Reveals the Diversity Of Null Almentioning
confidence: 99%
“…Moreover, our results also demonstrated that the combination of zebrafish–human comparative cancer genomics and functional genetic studies in zebrafish is a powerful approach for a long‐lasting challenge for identifying novel cancer driver genes on large CNAs/aneuploid chromosomes. Considering the plethora of available zebrafish mutants from large‐scale forward genetic screens and convenient reverse genetics, such as TALEN and CRISPR, 89‐92 a relatively large number of candidate cancer driver genes can be functionally validated in vivo with a similar approach as demonstrated for the smarcad1a gene here.…”
Section: Discussionmentioning
confidence: 99%